Advancements and Challenges in Landmine Clearance and Disarmament - Sharma, Swati (International Journal of Advanced Research in Peace, Harmony and Education; Vol 8 No 2 (2023): International Journal of Advance Research in Peace, Harmony and Education, 2023)
Landmines continue to pose significant threats to civilian populations and hinder post-conflict development. This review article offers a comprehensive examination of the progress made in landmine clearance and disarmament efforts, providing a thorough analysis of technological innovations, international collaborations, and the persistent challenges encountered in the pursuit of a mine-free world. Taking stock of developments up to the year 2023, the review delves into the multifaceted nature of landmine-related issues, exploring the evolving landscape of technologies used in clearance operations, the dynamics of global partnerships, and the intricate policy frameworks shaping the disarmament agenda. This article also sheds light on the humanitarian consequences of landmines, delving into their far-reaching impact on communities, economies, and public health. Additionally, it discusses successful case studies, policy considerations, and future prospects, offering a holistic perspective for policymakers, researchers, and practitioners working towards sustainable solutions in the realm of landmine clearance and disarmament.